Feasibility of using harvested rainwater as an alternative water source in a fluorosis endemic area in Puttalam District - Perera, A.M.I.R (My University, 2006)
The study was conducted to assess the feasibility of harvested rainwateras a source of low fluoride water in a fluorosis prevalent area in Puttalam District. This is a descriptive study conducted in the Inginimitiya PHI area in Puttalam District and comprised of three components. The first component involved the measurement of dental fluorosis dtatus in the area. This was measured by assessing all fifteen year old school children with life long residency in the area.